(untitled) (European Journal of Pure and Applied Mathematics, 2020)
This work is part of mathematical modeling and numerical analysis. This paper aims is to solve an advection problem where u=u(x; t) is the solution by Lax-Wendrof and nite dierence methods, to study the analytical stability in L2[0;1], L1[0; 1], then calculate the truncation error of these methods and nally study the analytical convergence of these methods. These numerical techniques of resolution were implemented in Scilab.